The Type I Versus Type II Agency Conflict on Earnings Management - Nurim, Yavida; Sunardi, Sunardi; Raharti, Rini (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2017)
Tis study aims to detect the background of earnings management behavior in which it shows the tendency of type I or II agency conflict. The high ownership concentration of firms in In-donesia leads type II agency conflict, but the good corporate governance formulation assumes conflict between management and shareholders. This study uses published data in IDX from 2009–2014. TThe result reveals that reputation quality has negative significant correlation to earnings management behaviors, but corporate governance quality has insignificant correlation to earnings management, except percentage of independent commissioner board in moder-ate level. It has implication that management faces type II agency conflict. The majority may monitor management directly, so the finding reveals that independent commissioner board’s function is not optimum as part of corporate governance mechanism. According to the evi-dence, corporate governance formulation, especially in Indonesia, should be needed for reduc-ing earnings management on type II tendency.